Performance effect of risk-based capital policy on insurers : longitudinal microdata evidence - Akpan, Sunday S.; Mahat, Fauziah; Amin Noordin, Bany Ariffin; Md Nassir, Annuar (Routledge, 2019)
Risk-based capitalization (RBC) is an insurance regulation policy aimed at protecting policyholders. But effects of this policy on insurers’ performance are conjectural as empirical studies are scarce. This study investigates RBC influence, in the context of capital structure, on return on asset (ROA), return on equity (ROE) and earnings per share (EPS) of insurers using 2SLS fixed and random effect models. From the results, RBC improved ROA and EPS significantly, but reduced ROE insignificantly. It concluded that RBC policy make a significant positive contribution to ROA and EPS. ROE is not significantly affected by RBC policy for the period under review.